The Value Of Amaranth Food Additives In The Food Industry - Dilshod Shodiev; Mohidil Abduvalieva (Zien Journals, 2023)
This article analyzes data on the composition and natural medicinal properties of the medicinal plant amaranth in the scientific, popular science literature, the beneficial properties of all vegetative organs of the plant (seed, leaf, body, root), etc. In addition, amaranth seeds contain squalene, tocotrienols and omega3,6,9, which can be used in medicine to treat many diseases.
Keywords: amaranth; oil; grain; nutrient content